2010
DOI: 10.1007/s10591-010-9131-5
|View full text |Cite
|
Sign up to set email alerts
|

What Factors Influence Therapy Drop Out?

Abstract: Are there systematic factors that predict client drop out in marriage and family therapy? Based on our review of literature we investigated the influence on drop out of personality characteristics such as hostility, anxiety, satisfaction with life, and self-esteem. We also investigated several demographic variables. The following variables were statistically significant predictors of client drop out: modality of treatment, marital status, occupation, income, and previous therapy experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 21 publications
0
13
2
Order By: Relevance
“…20%, up to 74%; Swift & Greenberg, 2012 ). Few predictors of dropout have emerged recurrently in research, such as low socio-economic status ( Reis & Brown, 1999 ), being married or living with a partner, previous experience with psychotherapy ( Werner-Wilson & Winter, 2010 ), low education ( Swift & Greenberg, 2012 ), older age ( Pomp, Fleig, Schwarzer, & Lippke, 2013 ), being African-American ( Lester, Artz, Resick, & Young-Xu, 2010 ), being female ( Shamir, Szor, & Melamed, 2010 ), suffering from low levels of anxiety and/or depression ( Baekeland & Lundwall, 1975 ), less clinical experience of therapists ( Roos and Werbart, 2013 , Swift and Greenberg, 2012 ) and weaker alliance ( Sharf, Primavera, & Diener, 2010 ). Still, most researchers who have investigated psychotherapy dropout agree that there is no clear evidence for a pattern of dropout predictors ( Baekeland and Lundwall, 1975 , Casares-López et al, 2011 , Swift and Greenberg, 2012 ).…”
mentioning
confidence: 99%
“…20%, up to 74%; Swift & Greenberg, 2012 ). Few predictors of dropout have emerged recurrently in research, such as low socio-economic status ( Reis & Brown, 1999 ), being married or living with a partner, previous experience with psychotherapy ( Werner-Wilson & Winter, 2010 ), low education ( Swift & Greenberg, 2012 ), older age ( Pomp, Fleig, Schwarzer, & Lippke, 2013 ), being African-American ( Lester, Artz, Resick, & Young-Xu, 2010 ), being female ( Shamir, Szor, & Melamed, 2010 ), suffering from low levels of anxiety and/or depression ( Baekeland & Lundwall, 1975 ), less clinical experience of therapists ( Roos and Werbart, 2013 , Swift and Greenberg, 2012 ) and weaker alliance ( Sharf, Primavera, & Diener, 2010 ). Still, most researchers who have investigated psychotherapy dropout agree that there is no clear evidence for a pattern of dropout predictors ( Baekeland and Lundwall, 1975 , Casares-López et al, 2011 , Swift and Greenberg, 2012 ).…”
mentioning
confidence: 99%
“…Interestingly, the only predictor of dropout found to be statistically significant in the current study was occupation, more specifically being unemployed. In prior research, lower income has been found to be a significant predictor of dropout in studies of clients with depression (Arnow et al, ; Beckham, ) and for clients attending marriage and family therapy (Werner‐Wilson & Winter, ). Furthermore, lower SES was found to be a significant predictor in two studies examining predictors of psychotherapy dropout (Braet et al, ; Chisholm et al, ).…”
Section: Discussionmentioning
confidence: 92%
“…Over the past 40 years, numerous studies have found that between 15% and 70% of clients drop out of therapy or do not complete a course of treatment to a satisfactory outcome (Baekeland & Lundwall, ; Edlund et al, ; Swift & Greenberg, ; Werner‐Wilson & Winter, ). The variance in this statistic stems from differences in the definition of dropout (i.e., clients who make some clinically meaningful progress and leave vs. clients who do not have any symptom reduction) or in the particular sample selected for investigation (Cooper & Conklin, ; Swift & Greenberg, ).…”
Section: The Problem Of Premature Client Dropoutmentioning
confidence: 99%